1993
DOI: 10.1002/art.1780360703
|View full text |Cite
|
Sign up to set email alerts
|

Biopsychosocial contributions to the management of arthritis disability

Abstract: of biopsychosocial aspects of arthritis were convened to participate.The purposes of the conference were as follows: 1) to review and synthesize the scientific literature on biopsychosocial aspects of arthritis disability, 2) to establish a research agenda to guide the scientific efforts of the research community and funding agencies, 3) to stimulate clinical applications of biopsychosocial strategies for the management of arthritis disability, and 4) to disseminate state-of-the-art scientific information to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The apparent relationships among depression, pain, and disability in RA argue for a biopsychosocial approach to RA management (27). Health care for persons with RA should extend beyond traditional rheumatologic approaches to embrace a genuine rehabilitative strategy, where the maximization of psychological and social functioning becomes a key treatment objective.…”
Section: Implications Of Depression For Rheumatologic Carementioning
confidence: 99%
“…The apparent relationships among depression, pain, and disability in RA argue for a biopsychosocial approach to RA management (27). Health care for persons with RA should extend beyond traditional rheumatologic approaches to embrace a genuine rehabilitative strategy, where the maximization of psychological and social functioning becomes a key treatment objective.…”
Section: Implications Of Depression For Rheumatologic Carementioning
confidence: 99%
“…Incorporation into clinical health care delivery of better theory regarding chronic disease and illness and better characterization of an individual’s disablement status can, however, improve diagnosis and treatment. Abundant evidence indicates the essential importance of using a biopsychosocial model for understanding the character of pain and of complex disorders such as TMD (9–20). The biopsychosocial model emphasizes that disease is not just a biological phenomenon but rather disease and its course are the result of an intersection of psychological and social factors with biological processes.…”
Section: Introductionmentioning
confidence: 99%
“…There is some evidence that the prevalence of depression may be lower among people with RA than with other rheumatic diseases such as systemic lupus erythematosus (SLE; Liang et al, 1984) and fibromyalgia (Walker et al, 1997), although these studies have methodological weaknesses (e.g., small samples). Recently reported estimates of the prevalence of depression among patients with RA range from 15% to 34%, with most studies reporting figures closer to the low end of this range (Creed & Ash, 1992;Creed, Murphy, & Jayson, 1990;DeVellis, 1993;Frank, Chaney, Clay, & Kay, 1991;Katz & Yelin, 1993). However, these figures are based primarily on selfreport scales measuring depressive symptoms rather than on diagnostic interviews or instruments administered by clinicians and therefore may be somewhat unreliable in capturing the true prevalence of depressive disorders in this population.…”
Section: Depressionmentioning
confidence: 99%
“…Yet many researchers continue to use cutoff scores obtained from one sample in a diagnostic fashion. A major assessment issue is the problem of criterion contamination, or the extent to which scales confound symptoms of depression with symptoms of rheumatic disease (DeVellis, 1993). A secondary analysis of data from three studies revealed that the CES-D overestimated the prevalence and severity of depressive symptoms among persons with RA, but the magnitude of this bias was modest (Blalock, DeVellis, Brown, & Wallston, 1989).…”
Section: Assessmentmentioning
confidence: 99%